HOW ARTIFICIAL INTELLIGENCE (AI) SUPPORTS UNDERGRADUATE STUDENTS’ ACADEMIC WRITING: EVIDENCE FROM INDONESIA - Wahyuningsih, Sri (Prominent, 2024)
Academic writing plays a crucial role in academics including undergraduate students. In addition, the development of technology provides effectiveness for them in the process of academic writing. The present study unravels undergraduate students’ voices on how artificial intelligence (AI) supports their academic writing including kinds of AI applications mostly used by them in enhancing academic writing and challenges in using AI. Anchoring in a qualitative research method, the data of this study were gathered from in-depth interviews with six students at an Indonesian higher education. The findings of the study revealed that AI applications are used to support students’ academic writing. Some AI applications they use include translation tools such as Google Translate, paraphrasing tools such as Quillbot, grammar and spelling checkers such as Grammarly, plagiarism checkers such as Turnitin, and reference management software such as Mendeley and Zotero. Furthermore, they reported that AI could enhance their academic writing by providing better organization, efficiency, consistency, and accuracy. However, critical thinking skills cannot be developed by AI applications. Thus, the finding of the study offers an implication that students can utilize these AI applications to support their work and they should actively participate in the process of academic writing.